Short-term visual performance of soft multifocal contact lenses for presbyopia - Sha,Jennifer (2016)
ABSTRACT Purpose: To compare visual acuity (VA), contrast sensitivity, stereopsis, and subjective visual performance of Acuvue® Oasys® for Presbyopia (AOP), Air Optix® Aqua Multifocal (AOMF), and Air Optix® Aqua Single Vision (AOSV) lenses in patients with presbyopia. Methods: A single-blinded crossover trial was conducted. Twenty patients with mild presbyopia (add ≤+1.25 D) and 22 with moderate/severe presbyopia (add ≥+1.50 D) who wore lenses bilaterally for 1 h, with a minimum overnight washout period between the use of each lens. Measurements included high- and low-contrast visual acuity (HCVA and LCVA, respectively) at a distance, contrast sensitivity (CS) at a distance, HCVA at intermediate (70 cm) and near (50 cm & 40 cm) distances, stereopsis, and subjective questionnaires regarding vision clarity, ghosting, overall vision satisfaction, and comfort. The test variables were compared among the lens types using repeated-measures ANOVA. Results: Distance variables (HCVA, LCVA, and CS) were significantly worse with multifocal lens than with AOSV lens (p≤0.008), except for AOMF lens in the mild presbyopia group in which no significant difference was observed (p>0.05). Multifocal lenses had significantly greater HCVA at 40 cm than AOSV lens (p≤0.026). AOMF lens had greater intermediate HCVA than AOP lens (p<0.03). AOP lens demonstrated greater improvements in stereopsis than AOMF and AOSV lens in the moderate/severe presbyopia group (p≤0.03). Few significant differences in subjective variables were observed, with no significant difference in the overall vision satisfaction observed between lens types (p>0.05). The proportions of patients willing to buy AOSV, AOMF, and AOP lenses were 20%, 40%, and 50%, respectively, in the mild presbyopia group and 14%, 32%, and 23%, respectively, in the moderate/severe presbyopia group; however, these differences were not statistically significant (p≥0.159). Conclusions: Further development of multifocal lenses is required before significant advantages of multifocal lenses over single vision lens are observed in patients with presbyopia.